Mathematical Connection Ability Profile of Junior High School Students of Comparative Materials - Syifa Maharani Priharvian; Tasya Alma Qolbi; Sintha Sih Dewanti (AL-ISHLAH: Jurnal Pendidikan, 2023)
Mathematical connection ability is needed because it relates to students' problem-solving abilities. This research was conducted to determine the ability of junior high school students' mathematical connections based on the region in the comparative material. This study uses the Manova test, which begins with quantitative research and continues with qualitative research. A sample of 251 students was taken using a cluster random sampling technique in one of the provinces in Indonesia with the most immigrants aiming to pursue education at various levels. The test instrument in this study was used to measure the ability of mathematical connections between mathematical ideas, mathematical connections with everyday life, and mathematical connections with other disciplines. The results of the Manova test show that the school environment affects students' mathematical connection abilities. In different areas, students have their own advantages in each mathematical connection indicator. So, it is suggested that schools pay attention to the learning methods used to suit students to improve students' mathematical connection abilities.